Một số kết quả quan trắc biến động thấm trong cấu trúc đê bằng công nghệ địa điện đa cực và phân cực kích thích - Cánh, Trần; Tuyến, Đoàn Văn; Văn, Phan Thị Kim; Weller, A.; Moeller, M. (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Monitoring results on permeable changes of dike structure by geoelectrical multi-electrods induced polarisation technology This paper presents a part of dike monitoring system to observe dike structure by geo-electrical multi-electrodes technology and induced polarization, which has been installed at significant weak points of the Red River’s dike in Thai Binh province. The primary results show : a) The monitoring system with the electrodes array installed at dike body is operating smoothly ; b) The daily changes on resistivity structure of dike’s soil layers at the flooding time were small, from -20 to +5 % ; Monthly changes determined from -65 to +15 % in comparison those in the dry time ; c) Based on the observed resistivity images the permeable changes from the river through the dike body at flooding time have been determined.